Impact Of Economic Digitalization On Labor Market Subjects - Babakulov Bahrankul Mamatkulovich; Mirzaxodjayev Alisher Botirovich (Universitas Muhammadiyah Sidoarjo, 2022)
In the context of digitalization, it is important to determine the characteristics of the labor market. This is because identifying the impact of digitalization on the labor market, highlighting its pros and cons, and eliminating the risk to labor relations provide an opportunity to address the unemployment caused by digitalization.